Trametes elegans: Sources and Potential Medicinal and Food Applications - Arivananthan Kanakasundar; Nurzafirah Mazlan; Ruzaina Ishak (Fakulti Perubatan dan Sains Kesihatan, UPM, 2023)
The emergence of microfungi medicinal applications represents a turnover in the drug discovery field. These microfungi species are found in rotten woods and leaf litters collected from forests and reserves in some tropical countries during rainy seasons. Among these species is Trametes elegans, which shares a commensalism-based relationship with the host (plants), offering protection against external invasions. Thus, Trametes elegans possesses unique compositional values and gained tremendous interest in the last decade for its promising applications, such as inhibiting a wide range of bacteria and harmful fungi, reducing oxidative stresses caused by free-radicals, nitric oxide, and hydrogen peroxide, as well as extending food shelf-life. This mini-review reports the available literature on Trametes elegans sources, studied extracts applications, and urges the investigation of other Trametes elegans potential applications as antiviral and anticancer agents.